Two-parameter families of discontinuous one-dimensional maps - Silva, Luis; Sousa Ramos, José (Annales Mathematicae Silesianae, 1999)
The aim of this paper is to establish the existence of a "box-within-a-box" bifurcation structure for monotone families of Lorenz maps and to study its combinatorics.